Macrobiotus rigidus sp. nov., new species of eutardigrade from New Zealand - Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2006)
Macrobiotus rigidus sp. nov. is a new species of eutardigrade from New Zealand very similar to M. coronatus de Barros, 1942. It is characterized by having a smooth cuticle, lacking eye spots, having three macroplacoids and a microplacoid, and eggs with conical processes (with reticular sculpture and an evident ring of basal digitations) and egg shell with dots that seem to continue the basal digitations.